RNP1, a new ribonucleoprotein gene of the yeast Saccharomyces cerevisiae. - Cusick, M E (1994)
A previously unidentified ribonucleoprotein (RNP) gene of yeast has been cloned and sequenced. The gene, named RNP1, was found adjacent to a previously sequenced gene encoding the second gene for ribosomal protein L4. RNP1 contains two RNA Recognition Motifs (RRM), [alternatively known as RNA binding Domains (RBD)], but unlike most RNP genes does not contain any auxiliary simple sequence domains. The first RRM (RRM1) most resembles RRM domains found in the hnRNP A/B class of RNP proteins. The second RRM (RRM2) most resembles a RRM so far seen only in the single RRM of the yeast SSB1 gene. Two null mutants of RNP1 that were created, a frameshift disruption and a complete deletion of the gene, were viable, demonstrating that the gene is not essential for cell growth. Two double null mutants of yeast RNP genes that were created (delta RNP1/delta SSB1 and delta SSB1/delta NPL3) were also viable. A fragment identical in size to the RRM1 domain could be amplified by PCR from the DNA of fungi, plants, and animals, using primers matching the ends of this domain, indicating that the structure of RRM1 is conserved. Another potential open reading frame on the same cloned fragment of DNA encodes a gene product whose structure resembles that of a seven-transmembrane-segment membrane receptor protein.